Analytical Effect of the Implementation of Business Ethics on the Success of Trading Companies - Ahmad Darda; Rojikun, Ahmad (Universitas Mohammad Husni Thamrin, 2026)
Trading companies in Indonesia currently play a strategic role in supporting the national economy. This contribution can be seen in the development of various forms of trading businesses, such as shops, convenience stores, supermarkets, and shopping centers (malls), which provide products from suppliers without undergoing a transformation process. In their operations, the application of business ethics is a crucial factor in maintaining business sustainability in the trading sector. Trading businesses experience intense competition due to the spread of businesses across various circles and the abundance of similar products. However, practices of violating business ethics still frequently occur, both by individuals and businesses, potentially disrupting business stability and continuity. Therefore, this study aims to analyze the application of business ethics in trading companies to ensure business sustainability. Business continuity is not only measured by a company's ability to generate profits, but also by the extent to which the company is able to survive and develop sustainably in the long term. This study uses a qualitative descriptive approach with data collection techniques through observation and literature study. The results show that trading companies that consistently apply business ethics principles tend to be able to avoid various operational risks, such as fraud, theft, and embezzlement, which have the potential to hinder business continuity.